Menstimulasi cara berpikir kritis dan kognitif pada Anak Usia 3-5 Tahun melalui permainan puzzle stick misteri : Studi Literatur: Menstimulasi cara berpikir kritis dan kognitif pada Anak Usia 3-5 Tahun melalui permainan puzzle stick misteri : Studi Literatur - Christina maria (Universitas PGRI Palembang, 2024)
Currently learning uses a student-centered approach. In reality, students' critical thinking abilities are still low. Advanced Puzzle Media is a learning media in the form of three-dimensional puzzles that can stimulate students to think critically and integrate with online material and questions. Therefore, the author innovated to create Advanced Puzzle media to improve students' critical thinking skills. In reality, students' critical thinking abilities are still low. This research aims to find out whether the use of puzzle stick media can improve students' critical thinking skills in PAI learning and how the use of puzzle stick media improves students' critical thinking skills in PAI learning. The use of stick puzzle media in improving students' critical thinking skills is through the pairing puzzle process.Problem solving is one of the aspects contained in the cognitive domain. Considering that young children are still in the learning stage of recognizing environmental conditions in their surroundings, including all existing problems, the learning activities provided refer to problem solving exercises. Children learn through playing, using puzzle media to train children's thinking skills in solving problems. The aim of this research is to determine the effect of using puzzle game media on children's problem solving abilities